The trees around you : how to identify common neighborhood trees in the Pacific Northwest - Clapp, Casey (Mountaineers Books, 2025)
"A visually rich, entertaining, and user-friendly field guide to identifying over 300 of the most common trees found in the Pacific Northwest's urban and suburban areas. Features 900-plus photos of bark, flowers, leaves, and more to clarify, compare, and contrast species"-- Provided by publisher.